HUBUNGAN ANTARA DISIPLIN BELAJAR DENGAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN SOSIOLOGI SMA N 1 RAMBATAN KECAMATAN RAMBATAN KABUPATEN TANAH DATAR - Darmila, Syintia - (Pendidikan Sosiologi, 2014)
This study uses a quantitative approach. This study is an ex-post factostudy using the technique of Pearson Product Moment Correlation test. Totalsample of 56 students of class X1, X2, X3, X4, and X5 in SMA 1 Rambatan.Sampling is done by proportional random sampling technique. Varible researchdiscipline consists of a variable (X) and Learning achievement variable (Y). Thetechnique of collecting data using questionnaires.The results showed that: there is a significant positive relationship betweenthe disciplines of student learning and the learning achievement of students ofclass X SMA Negeri 1 Rambatan district Tanah Datar West Sumatra of theacademic program 2013/2014, where the results r data = 0.388 greater than rcritical = 0.2632. And t test showed significance greater than t data= 2804 tcritical = 2.0048.